2000
DOI: 10.1002/(sici)1097-4644(20000701)78:1<62::aid-jcb6>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of aldolase B

Abstract: The localization of the aldolase B isozyme was determined immunohistochemically in rat kidney and liver using a polyclonal antibody. Aldolase B was preferentially localized in a nuclear region of hepatocytes from the periportal region and was absent in those from the perivenous region. Aldolase B was also preferentially localized in the proximal tubules and was absent in other structures of the renal cortex as well as in the renal medulla. Using reflection confocal microscopy, the enzyme was preferentially loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Previous studies in mammalian cells have shown that FBAs are located also in the nucleus of different cell types Dzugaj, 2004, 2008;Saez and Slebe, 2000). Precisely, it has been shown that aldolase A is located in the cytoplasm as well as in the nuclei of porcine cardiomyocytes and also of porcine and rat smooth muscle cells in heterochromatin regions Dzugaj, 2004, 2008).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Previous studies in mammalian cells have shown that FBAs are located also in the nucleus of different cell types Dzugaj, 2004, 2008;Saez and Slebe, 2000). Precisely, it has been shown that aldolase A is located in the cytoplasm as well as in the nuclei of porcine cardiomyocytes and also of porcine and rat smooth muscle cells in heterochromatin regions Dzugaj, 2004, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…The role of FBAs in cell nuclei remains unknown and is probably related with their involvement in a number of cellular processes unrelated with their primary function (see below). FBAs nuclear localization might be possible to link cellular metabolism with biological processes related with regulation of gene expression (Saez and Slebe, 2000). Moreover, we have shown that targeting of the AgtA aspartate-glutamate transporter in the plasma membrane of A. nidulans is strongly affected by low enzyme levels resulting from the low fbaA transcriptional levels.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations